A Chip‐Scale Oscillation‐Mode Optomechanical Inertial Sensor Near the Thermodynamical Limits. Issue 5 (8th April 2020) - Huang, Yongjun; Flor Flores, Jaime Gonzalo; Li, Ying; Wang, Wenting; Wang, Di; Goldberg, Noam; Zheng, Jiangjun; Yu, Mingbin; Lu, Ming; Kutzer, Michael; Rogers, Daniel; Kwong, Dim‐Lee; et al.
Abstract: Modern navigation systems integrate the global positioning system (GPS) with an inertial navigation system (INS), which complement each other for correct attitude and velocity determination. The core of the INS integrates accelerometers and gyroscopes used to measure forces and angular rate in the vehicular inertial reference frame. With the help of gyroscopes and by integrating the acceleration to compute velocity and distance, precision and compact accelerometers with sufficient accuracy can provide small‐error location determination. Solid‐state implementations, through coherent readout, can provide a platform for high performance acceleration detection. In contrast to prior accelerometers using piezoelectric or capacitive readout techniques, optical readout provides narrow‐linewidth high‐sensitivity laser detection along with low‐noise resonant optomechanical transduction near the thermodynamical limits. Here an optomechanical inertial sensor with an 8.2 µg Hz −1/2 velocity random walk (VRW) at an acquisition rate of 100 Hz and 50.9 µg bias instability is demonstrated, suitable for applications, such as, inertial navigation, inclination sensing, platform stabilization, and/or wearable device motion detection. Driven into optomechanical sustained‐oscillation, the slot photonic crystal cavity provides radio‐frequency readout of the optically‐driven transduction with an enhanced 625 µg Hz −1 sensitivity. Measuring the optomechanically‐stiffened oscillation shift, instead of the optical transmission shift, provides a 220× VRW enhancement over pre‐oscillation mode detection. Abstract : An optomechanical inertial sensor with an 8.2 µg Hz −1/2 velocity random walk at a 100 Hz data acquisition rate and a 50.9 µg bias instability is demonstrated, capable of precision acceleration measurements. Driven into optomechanical sustained‐oscillation, this inertial sensor provides radiofrequency readout of the optically‐driven transduction with enhanced 625 µg Hz −1 sensitivity, and a 43 dB dynamic range, in a solid‐state room‐temperature readout architecture.